A mind to stay : White plantation, Black homeland - Nathans, Sydney (Harvard University Press, 2017)
A Mind to Stay is a unique and extraordinary historical narrative of generations of a Black family with roots in slavery and in the South. This family won their freedom with emancipation but, instead of fleeing the poverty and oppression of the White plantation, decided to stay on the homeland of their White masters and then to purchase it for themselves within a decade. In a true counterpoint to the predominant tale of the Black exodus north in the late nineteenth and early twentieth century, these African Americans chose to hold onto the land that they had rightfully inherited and to risk all to keep it in the ensuing decades. Sydney Nathans, in his deep research into family and plantation papers and archives, as well as in invaluable oral interviews, has uncovered a slice of history that would otherwise have remained unknown. It is the story of a White plantation, Cameron Place, its owners who kept their slaves in family units, and who then sold their plantation to the same families in the 1870s. Those land-owning Blacks chose to remain on their land in the South through the tumultuous years of Reconstruction and Jim Crow and to claim all the rights due to a landowner up to the present. It is an unusual and original story told with great sensitivity and poignancy by Nathans who has the perseverance of a detective in seeking out the hidden tale and the skills and empathy of the historian in relating it.--